Role of adipose triglyceride lipase (PNPLA2) in protection from hepatic inflammation in mouse models of steatohepatitis and endotoxemia. Issue 3 (28th January 2014) - Jha, Pooja; Claudel, Thierry; Baghdasaryan, Anna; Mueller, Michaela; Halilbasic, Emina; Das, Suman K.; Lass, Achim; Zimmermann, Robert; Zechner, Rudolf; Hoefler, Gerald; Trauner, Michael
<x xml:space="preserve">Abstract</x> Hepatic inflammation is a key feature of progressive liver disease. Alterations of fatty acid (FA) metabolism and signaling may play an important role in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) and its progression to nonalcoholic steatohepatitis (NASH). Moreover, FAs activate peroxisome proliferator‐activated receptor α (PPARα) as a key transcriptional regulator of hepatic FA metabolism and inflammation. Since adipose triglyceride lipase (ATGL/PNPLA2) is the key enzyme for intracellular hydrolysis of stored triglycerides and determines FA signaling through PPARα, we explored the role of ATGL in hepatic inflammation in mouse models of NASH and endotoxemia. Mice lacking ATGL or hormone‐sensitive lipase (HSL) were challenged with a methionine‐choline‐deficient (MCD) diet as a nutritional model of NASH or lipopolysaccharide (LPS) as a model of acute hepatic inflammation. We further tested whether a PPARα agonist (fenofibrate) treatment improves the hepatic phenotype in MCD‐ or LPS‐challenged ATGL‐knockout (KO) mice. MCD‐fed ATGL‐KO mice, although partially protected from peripheral lipolysis, showed exacerbated hepatic steatosis and inflammation. Moreover, ATGL‐KO mice challenged by LPS showed enhanced hepatic inflammation, increased mortality, and torpor, findings which were attributed to impaired PPARα DNA binding activity due to reduced FABP1 protein levels, resulting in impaired nuclear FA import. Notably, liganding PPARα through fenofibrate attenuated hepatic inflammation in both MCD‐fed and LPS‐treated ATGL‐KO mice. In contrast, mice lacking HSL had a phenotype similar to the WT mice on MCD and LPS challenge. Conclusion: These findings unravel a novel protective role of ATGL against hepatic inflammation which could have important implications for metabolic and inflammatory liver diseases. (Hepatology 2014;59:858–869)